ZVS Buck-Boost LLC cascade converter with all soft switched switches. Issue 6 (3rd June 2019) - Zhu, Junjie; Qian, Qinsong; Zhan, Chengwang; Lu, Shengli; Sun, Weifeng
ABSTRACT: A Buck-Boost LLC cascade converter is proposed in this paper. In virtue of the Zero-Voltage-Switching (ZVS) modulation strategy for Buck-Boost circuit, all the switches can be soft switched with wide conversion range and full load range. By sharing one of the two bridge legs, the magnetizing current needed to realize the ZVS of switches decreases. Then, the power density and efficiency of the proposed converter increase. Theoretical analysis and characteristics of the proposed converter are presented and verified on a 210 V–400 V input 12 V/400 W output experimental prototype. The experimental results show that the proposed converter can achieve a peak efficiency of 95.6% at 1 MHz. The power density of the proposed converter is as high as 414 W/in 3 with the help of GaN transistors and planar transformers.